2017
DOI: 10.1055/s-0043-113440
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal fibrosis in achalasia patients is a rare cause of aborted peroral endoscopic myotomy procedures

Abstract: Peroral endoscopic myotomy (POEM) is now an established treatment for esophageal achalasia. The standard protocol ensures a smooth operation in most patients, but technical challenges and failures exist and little is known about the incidence, causes, and impact of aborted procedures. Here, using a large patient cohort, we attempted to answer these questions. All patients admitted for planned POEM between August 2010 and July 2015 underwent chart review. Aborted POEM was defined as the inability to finish the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 25 publications
5
41
0
Order By: Relevance
“…The PDS was shown to correlate well with procedural velocity and is an accurate measure of procedural difficulty. It has previously been shown that operative time indirectly correlates with complications . This supports the theory that the PDS will also correlate with complication rate.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The PDS was shown to correlate well with procedural velocity and is an accurate measure of procedural difficulty. It has previously been shown that operative time indirectly correlates with complications . This supports the theory that the PDS will also correlate with complication rate.…”
Section: Discussionsupporting
confidence: 76%
“…Variables such as fibrosis, orientation, and spastic contractions have been reported to impact the performance of POEM . The PDS was created based on expert consensus within our group of POEM operators in addition to the variables previously described in the literature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations